Small Scale Enterprise Development - Iskandar, Firsta Jusra (Journal of Regional and City Planning, 2000)
For some decades, small-scale enterprise has been instrumental for economic growth, poverty alleviation and the promotion of more pluralist societies. For the whole economics system, small-scale enterprise may be regarded as ‘safety valve’ since it guarantees people feeling of having a job and reduces the level of insecurity. The success of small-scale enterprise development depends on the support from the government and other stake holders.